2022
DOI: 10.1177/10778012221092477
|View full text |Cite
|
Sign up to set email alerts
|

More Talent, More Leeway: Do Violence Against Women Arrests Really Hurt NFL Player Careers?

Abstract: This article examines whether arrests for an act of violence against women have a negative impact on National Football League (NFL) player careers and whether this impact has become more negative over time. Framed by criminological deterrence and conflict theories, I conduct a Bayesian multi-level negative binomial regression on a matched pairs sample of all 117 NFL players arrested for an act of violence against women between 2000 and 2019 ( n = 234). Results show that the effect of an arrest on player career… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Topics of research relating to football are broad, ranging from performance to injury-related topics 4 , 17 , 56 , 107 to social and political issues. 38 , 101 , 103 With such a wide scope of research, it has become difficult to identify the most significant and impactful findings relating to football injuries. Bibliometric analyses provide a way to condense this ever-growing research, as articles with a greater number of citations are often considered the most influential in a field, and bibliometric citation analyses provide quantitative representation of an article’s impact.…”
mentioning
confidence: 99%
“…Topics of research relating to football are broad, ranging from performance to injury-related topics 4 , 17 , 56 , 107 to social and political issues. 38 , 101 , 103 With such a wide scope of research, it has become difficult to identify the most significant and impactful findings relating to football injuries. Bibliometric analyses provide a way to condense this ever-growing research, as articles with a greater number of citations are often considered the most influential in a field, and bibliometric citation analyses provide quantitative representation of an article’s impact.…”
mentioning
confidence: 99%
“…Though it is not clear whether athletes commit more acts of violence than those in the general population (Kreager, 2007), male athlete violence, and specifically male sexual and domestic violence against women (hereafter ‘VAW’) frequently makes headlines in sports news (Anderson, 2017). While studies have shown that, contrary to popular belief, the careers of athletes arrested for an act of VAW are not systematically negatively impacted by arrests (Sailofsky, 2023; Sailofsky and Shor, 2022), some accused athletes are released from their employment with an organization, as the team purports to ‘take a stand’ against their violent behaviour. While an optimistic reading of these team decisions might suggest that sport organizations assess the facts of the case and make employment decisions based on whether the player actually engaged in the alleged violent behaviour, a cursory glance at arrested athletes’ careers following arrests reveal that the veracity of the allegation and the harm caused by the alleged behaviour are far from the only factors considered.…”
Section: Introductionmentioning
confidence: 83%
“…While team decision makers all noted that VAW was unacceptable, and nearly all of them mentioned this type of physical violence when asked about more severe crimes, the actions taken by teams regarding accused players mostly tell a different story (Sailofsky, 2023; Sailofsky and Shor, 2022). If organizations had a zero-tolerance, morality-based policy to criminality or to VAW, the talent and productivity of a player would not have any impact on a player’s evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations